Induced abortion: incidence and trends worldwide from 1995 to 2008 - Sedgh, Gilda; Singh, Susheela; Shah, Iqbal H; Åhman, Elisabeth; Henshaw, Stanley K; Bankole, Akinrinola (The Lancet (British edition), 2012)
Data of abortion incidence and trends are needed to monitor progress toward improvement of maternal health and access to family planning. To date, estimates of safe and unsafe abortion worldwide have only been made for 1995 and 2003. We used the standard WHO definition of unsafe abortions. Safe abortion estimates were based largely on official statistics and nationally representative surveys. Unsafe abortion estimates were based primarily on information from published studies, hospital records, and surveys of women. We used additional sources and systematic approaches to make corrections and projections as needed where data were misreported, incomplete, or from earlier years. We assessed trends in abortion incidence using rates developed for 1995, 2003, and 2008 with the same methodology. We used linear regression models to explore the association of the legal status of abortion with the abortion rate across subregions of the world in 2008. The global abortion rate was stable between 2003 and 2008, with rates of 29 and 28 abortions per 1000 women aged 15–44 years, respectively, following a period of decline from 35 abortions per 1000 women in 1995. The average annual percent change in the rate was nearly 2·4% between 1995 and 2003 and 0·3% between 2003 and 2008. Worldwide, 49% of abortions were unsafe in 2008, compared to 44% in 1995. About one in five pregnancies ended in abortion in 2008. The abortion rate was lower in subregions where more women live under liberal abortion laws (p<0·05). The substantial decline in the abortion rate observed earlier has stalled, and the proportion of all abortions that are unsafe has increased. Restrictive abortion laws are not associated with lower abortion rates. Measures to reduce the incidence of unintended pregnancy and unsafe abortion, including investments in family planning services and safe abortion care, are crucial steps toward achieving the Millennium Development Goals. UK Department for International Development, Dutch Ministry of Foreign Affairs, and John D and Catherine T MacArthur Foundation.